The influence of relational capital and social capital on the infrastructure project performance in UAE - Almuharrmi, Sulayem Saleh Musallam Saeed; Mohamad, Norhidayah (Ascociacion Internacional de Economia Aplicada, 2021)
Most managers believe that their current structures are effective or highly effective in achieving business goals by relying on the traditional capital. Yet, many infrastructure project organizations in the UAE revolve around traditional and functional structures which are lack both the flexibility required to adapt to the changing business landscape and the capability to achieve end results effectively. Thus, this study strives to fill this gap by testing the role of relational and social capital on infrastructure project performance. This study has applied the quantitative approach to collect the data through a questionnaire instrument from 335 respondents. This study has found that there are positive and significant relationships between relational capital and social capital with the performance of public infrastructure projects in the UAE.